A Recent Update on Histiocytic Disorder in Children: Focus on Diagnosis and Treatment - Hoi Soo Yoon (The Korean Society of Pediatric Hematology-Oncology, 2020)
The histiocytosis is rare disorder characterized by the accumulation of macrophages, dendritic cells, or monocyte-derived cells in various tissues and organs of children and adults. Classifying histiocytic disorders is difficult and has changed over time as an understanding of the biology of these cells has evolved. The most recently revised 2016 WHO classification of histiocytosis and neoplasms of the macrophage-dendritic cell lineages has proposed grouping this diverse group of over 100 clinical entities into five main groups based on clinical, histologic, and molecular relevance. Comprehensive genomic studies for histiocytosis have been described and our understanding of the pathogenesis and biology has increased over the past decade. These advances will be able to make precision medicine and targeted therapy possible in patients with histiocytosis. Among the histiocytosis, this review mainly focuses on the updated diagnosis and treatment of Langerhans cell histiocytosis (LCH) and hemophagocytic lymphohistiocytosis (HLH) in children.